Pengaruh Metode Latihan Terbimbing Berbantuan Media Animasi terhadap Keterampilan Menulis Karangan Sederhana Bahasa Indonesia Siswa Kelas III SDN 08 Pontianak Selatan - Nur Fitri Meliani; Asmayani Salimi; Dyoty Auliya Vilda Ghasya (Journal on Education, 2024)
This study generally aims to analyze the effect of guided practice method assisted by animation media on the writing skills of simple Indonesian essays of third grade students of SDN 08 South Pontianak. This research used experimental research method with quasi experimental design. The sampling used was simple random sampling. Measurement technique was used in this study as a data collection technique in the form of a test. Based on statistical calculations, the control class post-test result was 64.00 while the experimental class post-test result was 79.43. The results showed that there was a difference in students' simple essay writing skills between after and before applying the guided practice method assisted by animated media. Previously, students' simple essay writing skills were still low, there were many writing errors and lack of skill in finding ideas for the essay. After applying the guided practice method assisted by animated media, students' essay writing improved and students' motivation in finding simple essay ideas increased. Thus, based on the results of hypothesis testing, it can be concluded that there is an effect of applying the guided practice method assisted by animated media on the writing skills of simple Indonesian essays of third grade students of SDN 08 South Pontianak.